A novel co‐infection model with Toxoplasma and Chlamydia trachomatis highlights the importance of host cell manipulation for nutrient scavenging. (27th November 2012) - Romano, Julia D.; de, Catherine; Carrasco, Jose A.; Ehrenman, Karen; Bavoil, Patrik M.; Coppens, Isabelle
Summary Toxoplasma and Chlamydia trachomatis are obligate intracellular pathogens that have evolved analogous strategies to replicate within mammalian cells. Both pathogens are known to extensively remodel the cytoskeleton, and to recruit endocytic and exocytic organelles to their respective vacuoles. However, how important these activities are for infectivity by either pathogen remains elusive. Here, we have developed a novel co‐infection system to gain insights into the developmental cycles of Toxoplasma and C. trachomatis by infecting human cells with both pathogens, and examining their respective ability to replicate and scavenge nutrients. We hypothesize that the common strategies used by Toxoplasma and Chlamydia to achieve development results in direct competition of the two pathogens for the same pool of nutrients. We show that a single human cell can harbour Chlamydia and Toxoplasma. In co‐infected cells, Toxoplasma is able to divert the content of host organelles, such as cholesterol. Consequently, the infectious cycle of Toxoplasma progresses unimpeded. In contrast, Chlamydia's ability to scavenge selected nutrients is diminished, and the bacterium shifts to a stress‐induced persistent growth. Parasite killing engenders an ordered return to normal chlamydial development. We demonstrate that C. trachomatisenters a stress‐induced persistence phenotype as a direct result from being barred from its normal nutrient supplies as addition of excess nutrients, e.g. amino acids, leads to substantial recovery of Chlamydia growth and infectivity. Co‐infection of C. trachomatis with slow growing strains of Toxoplasma or a mutant impaired in nutrient acquisition does not restrict chlamydial development. Conversely, Toxoplasma growth is halted in cells infected with the highly virulent Chlamydia psittaci. This study illustrates the key role that cellular remodelling plays in the exploitation of host intracellular resources by Toxoplasma and Chlamydia. It further highlights the delicate balance between success and failure of infection by intracellular pathogens in a co‐infection system at the cellular level.